Analisis Pengaruh Lokasi, Kualitas Pelayanan, Dan Keberagaman Produk Terhadap Keputusan Pembelian Konsumen Di Luwes Kartasura - Wibowo, Edi, Imronudin, S.E, M.Si, Ph.D (2015)
Purpose of the research is to analyze effect of location, service quality, and variety of products on buying decisions of consumers in Luwes Department Store of Kartasura. Population of the research is visitors of Luwes Department Store of Kartasura. Fifty (50) respondents were taken as sample by using nonprobability sampling with accidental sampling approach. Analysis tools of the research are validity test, reliability test, normality test, multicolinearity test, heteroskedasticity test, linear regression analysis, determination coefficient (R2), F-test (model appropriateness test) and t-test (hypothesis test). Based on results of data analysis, it has been known that location variable had a positive and significant effect on the buying decision of consumers. It means that the higher consumer's perception on a product, the stronger it drives the consumers to make a buying decision. Service quality also had a positive and significant effect on the buying decision of consumers. It means the higher perception of a consumer, the consumer has a stronger driving to make a buying decision. Product variety was significantly and positively affecting the buying decision of consumers. It means that the higher consumer's perception on a product, the stronger it drives the consumers to make a buying decision. Value of R2 was 0.876 meaning that 87.6% of variations of the buying decisions can be explained by location variable (X1), service quality (X2), and product variety (X3). While, remains 12.4% were explained or affected by factors other than ones examined in the regression. Key words: Location, service quality, product variety, buying decision.